2019
DOI: 10.1021/acs.analchem.9b04167
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Fiber Analysis by Thermal Desorption/Pyrolysis-Direct Analysis in Real Time-Mass Spectrometry

Abstract: The thermal desorption/pyrolysis-direct analysis in real time-mass spectrometry (TD/Py-DART-MS) method was developed for the analysis of fibers in this study. The fiber samples were pyrolyzed with a temperature gradient and the pyrolysis products were determined by DART-MS. The pyrogram from the TD/Py-DART-MS fiber analysis was found to be associated with the physical properties such as the melting points. At the same time, the TD/Py-DART-MS allows the analyst to obtain the chemical information such as polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Textile fibers from clothing, home furnishings, and industrial fabric (such as tarps, ropes, and upholstery) can be one of the most abundant sources of forensic evidence at almost any crime scene. Typically, these fibers have some sort of colorant attached to them, which can make them an important piece of evidence used for the positive identification of a suspect [6–8]. The same concept can be applied to plastics, food, and painted objects (tool transfer residue or automobile chips/residues), which also contain colorants, either in the form of a dye or, more commonly, a pigment [9,10].…”
Section: Identification and Characterization Of Synthetic Dyes By Empmentioning
confidence: 99%
See 1 more Smart Citation
“…Textile fibers from clothing, home furnishings, and industrial fabric (such as tarps, ropes, and upholstery) can be one of the most abundant sources of forensic evidence at almost any crime scene. Typically, these fibers have some sort of colorant attached to them, which can make them an important piece of evidence used for the positive identification of a suspect [6–8]. The same concept can be applied to plastics, food, and painted objects (tool transfer residue or automobile chips/residues), which also contain colorants, either in the form of a dye or, more commonly, a pigment [9,10].…”
Section: Identification and Characterization Of Synthetic Dyes By Empmentioning
confidence: 99%
“…In the case of disperse dyes, a common practice for analysis and identification is the use of LC or LC‐MS with the sample extracted from the fiber [17,77,79,100,101]; however, several studies have shown that dyes can be identified with direct ionization methods [7,74]. DART uses a stream of heated metastable gas to vaporize and ionize analytes, sending them directly into the mass spectrometer for analysis [7,85]. This method generates real‐time mass spectra of a sample simply by holding the sample in front of the source, whether it is a pharmaceutical tablet, a dollar bill, or a textile fiber.…”
Section: Identification and Characterization Of Synthetic Dyes With Mmentioning
confidence: 99%
“…Nowadays, PHWE has become a popular green extraction technique for the extraction of various types of compounds from different types of environmental, food and plant materials. It has also been used for the extraction and removal of organic compounds from foodstuff and soils to ensure food safety and environmental monitoring [52]. PHWE is an alternative to organic solvent extraction which uses pressurized water to extract compounds at high temperature and controlled pressure.…”
Section: Pressurized Hot Water Extractionmentioning
confidence: 99%
“…There are some major advantages of PHWE since it reduces the consumption of organic solvents in extraction, water is available everywhere and is non-toxic, easily disposable and recyclable with minimum environmental difficulties. It is a low-cost method that is efficient in extracting less-polar organic compounds from a variety of matrices [52,57,58].…”
Section: Pressurized Hot Water Extractionmentioning
confidence: 99%
“…Nylons, also referred to as polyamides, are a group of synthetic polymers that are used to manufacture rope, fabric, carpet fibers, and more [ 1 ] Various kinds of nylons are differentiated based on their synthesis [ 2 ]. A few examples of the various nylons include nylons 6, 6/6, 11, etc.…”
Section: Introductionmentioning
confidence: 99%